A smart content store with logical table for named data networking in industrial internet of things environment. (September 2021) - Li, Zhuo; Zhou, Meili; Han, Zhengzhou; Liu, Jindian; Luo, Peng; Liu, Kaihua
Abstract: Named Data Networking (NDN) is one of the most promising proposals for future Industrial Internet of Things (IIoT) architecture, which supports the sharing and distribution of data by providing in-network caching capability via built-in Content Store. In this paper, a smart Content Store with Logical Table (CSLT) is conceived. CSLT not only support the cache replacements efficiently but also line-rate support the All Sub-Name Matching (ASNM) and the Exact Name Matching (ENM), which are the essential algorithms during the name lookup process in Content Store, through building the relationship among information packets during the inserting to reduce the lookup process. Evaluation results show that CSLT can speed up the single-thread throughput to 177.37 MPPS under the ASNM and the ENM. This type of framework can assist users to enhance sharing and transmission of manufacturing data in the IIoT environment, which can speed up product development or manufacturing processes.